Pengaruh Kompetensi Pegawai, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai : Studi pada Cabang Pelayanan Dinas Pendapatan Provinsi Wilayah Kabupaten Tasikmalaya - Ading Rahman Sukmara; Fajar Firmansyah; Ferey Herman (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research was motivated by the performance of employees in the Provincial Revenue Service Office of the Tasikmalaya District who were less likely to experience good improvement. Therefore research is needed in order to find the factors that influence employee performance. Variables that are thought to influence employee performance are employee competence, employee work discipline and work environment. The purpose of this study is to analyze the influence of employee competencies partially on employee performance, work discipline partially on employee performance, work environment partially on employee performance and employee competencies, work discipline and work environment simultaneously on employee performance. The subject of this study was the Provincial Revenue Service of the Tasikmalaya Regency Region with a population of all employees in the scope of the Provincial Revenue Office of the Tasikmalaya Regency. sampling from the population using a random sampling system or random sample with 35 respondents. Analysis of the data used is multiple regression analysis with the help of the SPSS program ver. 20. The results of this study indicate that employee competence partially has a significant effect on employee performance, work discipline partially has no significant effect on employee performance, the work environment partially has a significant effect on employee performance, and employee competence, work discipline and work environment simultaneously have a significant effect on performance of Tasikmalaya Regency Provincial Revenue Service staff employees.